A Theory of Fiduciary Liability - Miller, Paul (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2011)
The law of fiduciaries has been developed in an unprincipled manner. Consequently, the common law lacks a clear idea of the nature of the fiduciary relationship, the justification for fiduciary duties, and the purpose of fiduciary remedies. However, according to the author a principled theory of fiduciary liability may be derived from the common law. The focal point is the recent decision of the Supreme Court of Canada in Galambos v. Perez. The theory of liability suggested by Galambos and developed by the author is based on the conventional notion that fiduciary liability is premised upon the existence of a fiduciary relationship. The author argues that a clearer account of the nature and normative significance of the fiduciary relationship is critical to developing a sound understanding of the nature and scope of fiduciary duties. Under the theory developed by the author, the fiduciary relationship is treated as a distinctive kind of legal relationship. It is one in which one person (the fiduciary) wields discretionary power over the practical interests of another (the beneficiary). According to the author, fiduciary duties are explicable solely in terms of normatively salient qualities of the fiduciary relationship. The author explains these qualities and shows how they support and limit the incidence of fiduciary duties.